Kinetics changes in physicochemical quality attributes of Malaysian papaya cultivars during storage - Farouk Idnan, Umi Fahada (2018)
Papaya (Carica papaya L.) is a tropical climacteric fruit undergoes ripening significantly after harvest. The ripening process resulted in physicochemical changes where the rate increases with increasing storage temperature and the changes might be cultivar’s dependent. In the present study, the physicochemical changes of Eksotika II and Sekaki papaya that were stored at four different temperatures were evaluated and the kinetics changes was determined. The fruits were stored at four temperatures (10±1°C; 60±10%RH, 15±1°C; 60±10%RH, 20±1°C; 60±10%RH, and 25±2°C; 70±10%RH) and the physicochemical parameters namely weight loss, texture, colour, total soluble solid (TSS), pH and titratable acidity (TA) value, ascorbic acid, chlorophyll and pectin content were measured at two days interval for fruits stored at 10 and 15°C while fruits stored at 20°C and 25°C, the analysis was performed daily. The results showed that, peel colour changes for both Eksotika II and Sekaki cultivar increased during storage except for hue value. TSS, pH value, and ascorbic acid content also showed an increment with exception for pH value where the value decreased when stored at 25°C (Eksotika II cultivar) and at 20 and 25⁰C (Sekaki cultivar). Eksotika II cultivar showed the highest TSS value with significant (p<0.05) differences observed between low (10 and 15°C) and high (20 and 25°C) storage temperatures. Ascorbic acid content of Sekaki cultivar surprisingly showed percentages of increment more than Eksotika II cultivars. Attributes that showed decreasing pattern were textural (N) changes, weight loss (%) and chlorophyll (%) content. TA value and pectin (%) content did not show a clear trend and insignificance (p>0.05) in most of the storage temperatures. Kinetic reaction was determined for all quality attributes and fitted into zero and first order kinetic reaction. All quality attributes followed zero order kinetics reaction except ascorbic acid content that followed first order kinetics reaction. However, colour quality changes can both be used for zero and first order kinetic reaction. Best fitted data were further analysed into Arrhenius equation namely; weight loss (%), TSS, ascorbic acid content and hue value. It was found that activation energy (Eₐ) for both weight loss (%) and TSS value was higher in Eksotika II cultivar which is 46.37 and 84.15 kJ/mol respectively. On the other hand, ascorbic acid content and hue value showed lower activation energy (Eₐ) in Eksotika II cultivar which is 22.02 and 178.97kJ/mol respectively. It can be depicted that the lower the Eₐ value, will therefore increase the rate of reaction. Hence, the value of k and Eₐ can be used to predict the rate of degradation or synthesization of quality attributes at different temperatures.